1997
DOI: 10.1042/bj3220893
|View full text |Cite
|
Sign up to set email alerts
|

Secretory processing of amyloid precursor protein is inhibited by increase in cellular cholesterol content

Abstract: Plasma-membrane composition plays a crucial role in most of the cellular functions that depend on membrane processes. In virtually all cell types the proteolytic processing of Alzheimer amyloid precursor protein (APP) to generate soluble APP (sAPP) is believed to occur at the plasma membrane or in its immediate proximity. Alteration of this metabolic pathway has been linked to the pathogenesis of Alzheimer's disease. We analysed the effect of membrane cholesterol enrichment on APP metabolism. Incubation of COS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(101 citation statements)
references
References 53 publications
5
95
0
Order By: Relevance
“…McLaurin et al 44 reported that membrane cholesterol inversely correlated with the extent of Ab 1 -40 and Ab 1 -42 bilayer interaction and Gibson-Wood et al 45 found that distribution of cholesterol rather than the total mass is what regulates Ab genesis. Racchi et al 46 showed that membrane sterol enrichment by incubation with cholesterol-rich b-VLDL caused a dose-dependent inhibition of Ab release. In transgenic mice expressing the Swedish familial AD mutations, changes in concentrations of sAPP and Ab in brain were all negatively correlated with serum cholesterol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…McLaurin et al 44 reported that membrane cholesterol inversely correlated with the extent of Ab 1 -40 and Ab 1 -42 bilayer interaction and Gibson-Wood et al 45 found that distribution of cholesterol rather than the total mass is what regulates Ab genesis. Racchi et al 46 showed that membrane sterol enrichment by incubation with cholesterol-rich b-VLDL caused a dose-dependent inhibition of Ab release. In transgenic mice expressing the Swedish familial AD mutations, changes in concentrations of sAPP and Ab in brain were all negatively correlated with serum cholesterol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…CV, isolated from fresh eggs, were treated with cinnamycin and neomycin for 30 min (25°C) followed by fusion assays. For fusion recovery, CV suspensions (OD 405 1.0), isolated from Smst-/Atst-incubated eggs, were treated with 2 mM CHOL-loaded hpβcd or 200 μM αT for 30 min (25°C), centrifuged, and suspended in fresh BIM for fusion assays; CHOL-loaded hpβcd was prepared as described [27,42,70]. αT was delivered in hexadecane (<0.1% solvent, final) [26,27].…”
Section: Egg Manipulationsmentioning
confidence: 99%
“…by statin treatment) causes both an increase in the secretion of soluble APP (sAPP, a-secretase product) and a decrease in Ab production. 67,[69][70][71] Increasing membrane cholesterol decreases the secretion of sAPP, 72,73 possibly due to cholesterol interfering with glycosylation in the protein secretory pathway. 74 As sAPP is thought to have neurotrophic properties, decreasing sAPP levels may promote neurodegeneration.…”
Section: Cholesterol and Cad As Ad Risk Factorsmentioning
confidence: 99%